Joannici wobec zagrożenia Nowej Marchii wyprawami husyckimi w latach 1432-1433 = Knights of the Order of St John of Jerusalem against the New March threatened bythe Hussite expeditions, 1432-1433 - Karp, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The history of the presence of the Knights of the Order of St John of Jerusalem on the territaryof the New March dates back to the 14th century. According to the resolutions of the agrement signed in Cremmen in 1318 Waldemar, Margrave of Brandenburg, allowed Knights of the Order of St John of Jerusalem to take over the contemporary estate of the Knights of the Temple of Solomon which was closed down a few years earlier. Knights of the Order of St John of Jerusalem came in to possession of the estate of Santok located on Greater Poland and Brandenburg borderland in circa1397 when Sigismung of Luxemburg pledged it for 300 grzywna (units). It was the contemporary castle that played an important role during the Polish-Hussite expedition against the Order ofTeutonic Knights in 1433.
Keywords: Zakon Rycerzy Jerozolimskiego Szpitala św. Jana Chrzciciela; Santok (pow. gorzowski) - historia; Nowa Marchia; husyci; historia - 14-15 w.